Colombia : Request for Augmentation of Access Under the Flexible Credit Line Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2020)
The current FCL arrangement for Colombia was approved in May 2020. Colombia was cited for its very strong policy frameworks-anchored by a flexible exchange rate, a credible inflation-targeting regime, effective financial sector supervision and regulation, and a structural fiscal rule-and a track record of very strong policy implementation that served as a basis for the economy's resilience prior to the Covid-19 pandemic.